2020
DOI: 10.1038/s41598-020-65822-3
|View full text |Cite|
|
Sign up to set email alerts
|

Baseline and Disease-Induced Transcriptional Profiles in Children with Sickle Cell Disease

Abstract: Acute chest syndrome (ACS) is a significant cause of morbidity and mortality in sickle cell disease (SCD), but preventive, diagnostic, and therapeutic options are limited. Further, ACS and acute vasoccclusive pain crises (VOC) have overlapping features, which causes diagnostic dilemmas. We explored changes in gene expression profiles among patients with SCD hospitalized for VOC and ACS episodes to better understand ACS disease pathogenesis. Whole blood RNA-Seq was performed for 20 samples from children with SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…T-cell lymphopenia-associated inflammatory responses have been previously linked to the inactivation of PI3Kδ and PI3Kγ 27 , genes that were found to be downregulated in a previous 25 meta-analysis in SCD. Concomitant suppression of genes related to adaptive immune responses (B and T cell signalling) was also observed during the two complications of SCD, acute chest syndrome (ACS) and acute vaso-occlusive pain crises (VOC) in the study from Creary et al 8 We found Th1 and Th2 cell differentiation and Th17 cell differentiation to be significantly enriched downregulated KEGG pathways for treated SCD patients in comparison to HC (Figure 3 and Supplementary Figure 3). This result might suggest a contribution to the altered immune response, potentially leading to an increased risk of severe bacterial infections among SCD patients.…”
Section: Discussionmentioning
confidence: 62%
“…T-cell lymphopenia-associated inflammatory responses have been previously linked to the inactivation of PI3Kδ and PI3Kγ 27 , genes that were found to be downregulated in a previous 25 meta-analysis in SCD. Concomitant suppression of genes related to adaptive immune responses (B and T cell signalling) was also observed during the two complications of SCD, acute chest syndrome (ACS) and acute vaso-occlusive pain crises (VOC) in the study from Creary et al 8 We found Th1 and Th2 cell differentiation and Th17 cell differentiation to be significantly enriched downregulated KEGG pathways for treated SCD patients in comparison to HC (Figure 3 and Supplementary Figure 3). This result might suggest a contribution to the altered immune response, potentially leading to an increased risk of severe bacterial infections among SCD patients.…”
Section: Discussionmentioning
confidence: 62%
“…T-cell lymphopenia–associated inflammatory responses have been previously linked to the inactivation of PI3Kδ and PI3Kγ 37 , genes that were found to be downregulated in a previous 16 meta-analysis. Concomitant suppression of genes related to adaptive immune responses (B and T cell signalling) was also observed during the two complications of SCD, acute chest syndrome (ACS) and acute vaso-occlusive pain crises (VOC) in the study from Creary et al 14 . We found Th1 and Th2 cell differentiation and Th17 cell differentiation to be significantly enriched downregulated KEGG pathways for treated SCD patients in comparison to healthy controls (Figure 3A-C).…”
Section: Discussionmentioning
confidence: 85%
“…A better understanding of SCD pathophysiology and its complex manifestation is needed to develop targeted new treatment modalities that may also be more widely available to patients 14 . To this end, we analysed gene expression profiles from children with SCD, treated with HU or untreated, in comparison to healthy controls in an erythropoiesis in vitro model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations